ASSESSING MUSCULOSKELETAL DISORDERS (MSDS) OF WORKERS OF FIRED CLAY BRICKS INDUSTRY - Tri Budiyanto; Okka Adiyanto; Farid Ma'ruf; Hari Haryadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Ergonomics is important for sustainable development in many fields, including architecture, health, product design, safety, and workplace design. Ergonomic assessments are essential in the workplace to prevent musculoskeletal disorders (MSDs). Currently, Indonesia has a standardized ergonomic assessment, SNI 9011:2021. This assessment standard is widely used to evaluate human posture. This study aims to evaluate the position of a traditional brick-maker in which the posture identification system is based on the SNI 9011:2021. This study employed a cross-sectional design with a sample of workers in conventional brick manufacturing. The primary findings of this study were visual ergonomic assessment for posture identification, identification of ergonomic assessment categories with high risk in brick manufacturing, and the prevalence of nagging pain among workers in the brick moulding and drying process. To reduce occupational ergonomic risk, particularly for brick-making workers, ergonomic intervention is required in the form of additional work aids such as chairs. This has been shown to reduce the evaluation score based on SNI 9011: 2021, thereby reducing the occurrence of musculoskeletal disorders